Nematode Management for Golf Courses in Florida - William T. Crow (EDIS)
Revised! EENY-008, a 9-page illustrated fact sheet by William T. Crow, explains what plant-parasitic nematodes are, how they affect turf, how to know if they are a problem, and how to manage them on a golf course. Published by the UF Department of Entomology and Nematology, April 2010.